"Cherimoya-like" polysilsequioxane microspheres with structure-enhanced spectral capability for passive daytime radiative cooling. (August 2022) - Zuo, Tian; Zhang, Jiawen; Zhong, Shenjie; Xu, Tianqi; Xu, Lang; Xu, Shuai; Pan, Bicheng; Cai, Ying; Yi, Lingmin
Abstract: Passive daytime radiative cooling (PDRC) is a promising technique that can cool a surface without any energy consumption by reflecting sunlight and radiating heat to the outer space. While some sophisticated radiative coolers have been made, it still remains a great challenge in fabricating highly efficient, low-cost and scalable radiative cooling materials. Herein, a serious of inexpensive and widely available single-material polysilsequioxane (PSQ) microspheres have been prepared for PDRC via a simple sol-gel method. The PSQ microsphere with numerous synapses on its surface can effectively improve the solar reﬂectance of PSQ coating (an average reflectivity of 93.83 %) through the optical synergy of Rayleigh scattering and Mie scattering. Moreover, these "cherimoya-like" PSQ microspheres containing Si-O-Si skeleton endow the PSQ coating with a high average emissivity of 94.29 %. The excellent PDRC capability is further demonstrated by applying PSQ to cotton fabric. Benefited from the stack structure and the spectral characteristics of PSQ microspheres, the hydrophobic PSQ treated cotton fabric realizes an efficient temperature reduction of 10.5 °C compared with pristine cotton fabric under direct solar irradiation. The PSQ microspheres with superior PDRC capability, which can be conveniently applied to diverse substrate, have great potential for radiative cooling applications. Graphical Abstract: ga1 Highlights: Widely available PSQ microspheres for PDRC are prepared by a facile sol-gel method. Cherimoya-like PSQ enhances solar reflectivity via a dual scattering mechanism. The PSQ with Si-O-Si backbone and organic constituent exhibits high IR emissivity. PSQ treated cotton fabric shows a PDRC of 10.5 °C lower than pristine cotton fabric.